Retrospective evaluation of the patients who were admitted to the emergency department of our hospital due to a brain aneurysm and operated by brain surgery clinic (Annals of Medical Research, 2021)
Aim: In this study, we aimed to evaluate the clinical features of brain aneurysms in patients who were admitted to the emergency department in our hospital.Material and Methods: The records of 91 patients who were admitted to the emergency department for any reason between 01.01.2013 and 01.01.2018 and diagnosed with a brain aneurysm after brain- CT-angiography together with aneurysm-related symptoms and were operated were retrospectively screened after the approval of the local ethics committee. The patients’ age, weight, sex, bleeding time, Glasgow coma scale (GCS), Fisher, Yasargil scores, complications, postoperative status, and the presence of diabetes mellitus were recorded. Brain-CT-angiography was used to record the localization of the aneurysm, its size,Fisher grading scale, projection, anatomical variation, whether it was multiple or incidental, he presence of intraventricular hemorrhage and SAH. Results: There was a statistically significant and strong negative correlation between GCS and Fisher and Yasargil classifications. There was a statistically significant and strong positive correlation between the post-op status of the patient and Fisher, Yasargil classifications and the complications.Conclusion: Whether the patients are admitted to the emergency department with clinical symptoms of an aneurysm or not, when the patients are diagnosed with an aneurysm, we believe that one of GCS, Fisher, or Yasargil classifications will reflect the patient’s clinical status, vasospasm status if SAH is present, post-op status, and complications. We think that the location, size, and projection of the aneurysms are related to the emerging complications and post-op status.Keywords: Brain aneurysm; surgical treatment; fisher classification; Yasargil classification.
Keywords: Brain aneurysm; surgical treatment; fisher classification; Yasargil classification.